Harmonized detail specification for fixed aluminium electrolytic capacitors (long-life grade). Non-solid electrolyte. Cylindrical, polar insulated metallic case, clamp or stud mounting screw terminations. Full plus additional assessment level. (15th March 1981) - British Standards Institution,
No abstract available